Cardiac abnormalities in familial palmoplantar keratosis. Issue 4 (October 1986) - Protonotarios, N; Tsatsopoulou, A; Patsourakos, P; Alexopoulos, D; Gezerlis, P; Simitsis, S; Scampardonis, G
Abstract : Cardiac abnormalities were identified in patients with familial palmoplantar keratosis. All of them were descended from families on the Greek island of Naxos. Four families were studied and nine cases of palmoplantar keratosis were identified; seven of them showed symptoms and signs of heart disease. Cardiomegaly on chest x ray and electrocardiographic abnormalities were common findings. Three cases had episodes of ventricular tachycardia and a fourth patient died suddenly. All patients with cardiac signs and symptoms showed echocardiographic enlargement of the right ventricle and a right ventricular band; in three the left ventricle was also affected.